Sentiment Analysis of Indonesian Citizen Tweets Using Support Vector Machine on the Rebranding of Twitter to X - Hakim, Bhustomy; Kinasih, Putri Rindu (Jurnal Tekno Kompak, 2024)
How other people see the world and assess it affects their opinions, their understanding of it, and the choices they make. As a result, when we need to make a choice, we frequently ask for other people's opinions. Sentiment analysis, also known as opinion mining, is a cost-effective way for businesses and individuals to gather information about public sentiment. In this research, the writers aimed to study Indonesian netizen’s sentiment towards the rebranding of Twitter to X. Obviously, it is impossible to ignore the name and logo changes. The blue and white bird logo on Twitter has become a symbol of the network's culture and lexicon for over ten years. The verb "tweet" has evolved to refer to a post. With 14.75 million Twitter users, which ranks Indonesia sixth in the world, the writer is intrigued to study more about how Indonesian citizens see the rebranding issue. The data scrapping which collects the tweets about Twitter rebranding into X is collected from July 23rd, 2023, when the rebranding news appeared, and July 31st, 2023, which focuses on the day of rebranding that occurred. And, for the feature extraction, we will be using the TD-IDF method and Support Vector Machine using Gaussian Radial Basis Function Kernel as the model. Afterward, in the evaluation phase, we are using Confusion Matrix to find accuracy, f1-score. Lastly, the sentiment will also be analyzed by using rebranding theory. The result of this research shows that the Indonesian netizens' neutral sentiments. This result is also strengthened by the word cloud results which mostly show general words such as rebranding, twitter, https, jadi, yang, and X.